2019
DOI: 10.3390/pr7050260
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Heterogeneity on Sorptivity in Sandstones with High and Low Permeability in Water Imbibition Process

Abstract: Capillary imbibition in unsaturated rocks is important for the exploitation of tight reservoirs, such as oil and gas reservoirs. However, the physical properties of natural rocks tend to be relatively uneven, mainly in the heterogeneity of material composition and pore space. Reservoir heterogeneity is an important factor affecting the exploitation of oil fields and other reservoirs, which can be evaluated by the pore structure tortuosity fractal dimension DT of rock. The greater the value of DT, the stronger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…On this basis, the stage fractal dimension of small pores and macropores of different samples are obtained (Zhang et al, 2022) (Figure 12A), In addition, the relationship between the stage pore fractal dimension and pore compressibility coefficient is analyzed (Figure 12B), It is found that reservoir pore compressibility coefficient has an obvious positive correlation with the fractal dimension D L of mesopores and macropores, while a negative correlation with the fractal dimension D s of micropores and micro mesopores. The pore fractal dimension is jointly controlled by the dispersion degree of reservoir pore size distribution and the complexity of the pore surface (Wu et al, 2019;Hu et al, 2020a). The Larger D L indicates fewer large pores developing in reservoirs and the reservoir total porosity is small, resulting in a large change rate of pore volume under a stress state, to present a large pore compression coefficient, but it does not mean that reservoir medium is easier to be compressed.…”
Section: Pore Heterogeneity Of the Reservoirmentioning
confidence: 99%
“…On this basis, the stage fractal dimension of small pores and macropores of different samples are obtained (Zhang et al, 2022) (Figure 12A), In addition, the relationship between the stage pore fractal dimension and pore compressibility coefficient is analyzed (Figure 12B), It is found that reservoir pore compressibility coefficient has an obvious positive correlation with the fractal dimension D L of mesopores and macropores, while a negative correlation with the fractal dimension D s of micropores and micro mesopores. The pore fractal dimension is jointly controlled by the dispersion degree of reservoir pore size distribution and the complexity of the pore surface (Wu et al, 2019;Hu et al, 2020a). The Larger D L indicates fewer large pores developing in reservoirs and the reservoir total porosity is small, resulting in a large change rate of pore volume under a stress state, to present a large pore compression coefficient, but it does not mean that reservoir medium is easier to be compressed.…”
Section: Pore Heterogeneity Of the Reservoirmentioning
confidence: 99%
“…The study of water migration by capillarity in calcite-based materials (such as limestones) by means of NR has gained considerable attention by the scientific community in recent years [25][26][27][28][29][30]. It has been successfully applied for the study of water movement by spontaneous imbibition in rocks [31][32][33], sandstones [34,35], concrete [36,37], and bricks [38]. Generally, a linear trend of the height of the water front (h(t)) with the square root of the exposure time is attained, according to the Lucas-Washburn (L-W) equation.…”
Section: Introductionmentioning
confidence: 99%
“…The fractal dimension reflects the validity of the space occupied by complex bodies, which is a measure of irregularity of complex shapes and bodies including the Hausdorff dimension, the box covering method, and so on. Consider a 3D space where two coordinates ( x , y ) represent a 2D position of each point in asphalt concrete, and the third coordinate ( z ) represents the optical intensity of image [34]; the 3D optical intensity is displayed in Figure 8a. The variation of intensity reflects the roughness of the surface and light absorptivity of the medium.…”
Section: Results Analysismentioning
confidence: 99%